PC Cable-Stayed Bridge Main Girder Shear Lag Effects: Assessment of Single Cable Plane in Construction Stage - Yan-feng Li; Xing-long Sun; Long-sheng Bao (Advances in Materials Science and Engineering)
A model test and finite element analysis were conducted in this study to determine the distribution law of shear lag effect in the main beam section, a box girder, during the cable-stayed bridge construction process. The experimental and theoretical results were compared in an example of loading the control section. The stress value of the cable tension area of the main beam upper edge was found to markedly change when tensiling the cable force and was accompanied by prominent shear lag effect. After a hanging basket load was applied, the main beam of certain sections showed alternating positive and negative shear lag characteristics. The shear lag distribution law in the box girder of the single-cable-plane prestressed concrete cable-stayed bridge along the longitudinal direction was determined in order to observe the stress distribution of the girder. The results show that finite element analysis of the plane bar system should be conducted at different positions in the bridge under construction; the calculated shear lag coefficient of the cable force acting at the cable end of the cantilever reflects the actual force. In the beam segments between the cable forces, the shear lag coefficient determined by the ratio of the bending moment to the axial force reflects the actual stress at the cable force action point. In the midspan beam section between the action points of cable forces, the shear lag coefficient of the bending moment reflects the actual stress. The section shear lag coefficient can be obtained by linear interpolation of the beam section between the cable action point and the middle of the span.